Influence of Hand Rearing and Bird Age on the Fecal Microbiota of the Critically Endangered Kakapo - Waite, David W.; Eason, Daryl K.; Taylor, Michael W. (Applied and environmental microbiology, 2014)
The critically endangered New Zealand parrot, the kakapo, is subject to an intensive management regime aiming to maintain bird health and boost population size. Newly hatched kakapo chicks are subjected to human intervention and are frequently placed in captivity throughout their formative months. Hand rearing greatly reduces mortality among juveniles, but the potential long-term impact on the kakapo gut microbiota is uncertain. To track development of the kakapo gut microbiota, fecal samples from healthy, prefledged juvenile kakapos, as well as from unrelated adults, were analyzed by using 16S rRNA gene amplicon pyrosequencing. Following the original sampling, juvenile kakapos underwent a period of captivity, so further sampling during and after captivity aimed to elucidate the impact of captivity on the juvenile gut microbiota. Variation in the fecal microbiota over a year was also investigated, with resampling of the original juvenile population. Amplicon pyrosequencing revealed a juvenile fecal microbiota enriched with particular lactic acid bacteria compared to the microbiota of adults, although the overall community structure did not differ significantly among kakapos of different ages. The abundance of key operational taxonomic units (OTUs) was correlated with antibiotic treatment and captivity, although the importance of these factors could not be proven unequivocally within the bounds of this study. Finally, the microbial community structure of juvenile and adult kakapos changed over time, reinforcing the need for continual monitoring of the microbiota as part of regular health screening.